Recognizing Atypical Parkinsonisms: “Red Flags” and Therapeutic Approaches - McFarland, Nikolaus R. (Semin Neurol, 2017)
The overlap of signs and symptoms between Parkinson disease and the atypical parkinsonian syndromes, such as progressive supranuclear palsy (PSP), multiple system atrophy (MSA), corticobasal degeneration (CBD), and dementia with Lewy bodies (DLB), can render clinical diagnoses challenging. The continued evolution of diagnostic criteria to reflect the increasingly recognized heterogeneous presentations of these diseases further complicates timely recognition and diagnoses. This review provides a diagnostic approach to the classic atypical parkinsonian syndromes (PSP, CBD, MSA, and DLB) with emphasis on the key clinical and pathological features of each and the recognition of “red flags” in the setting of recent advances in diagnosis and treatment.